2019
DOI: 10.1007/s10822-019-00194-z
|View full text |Cite
|
Sign up to set email alerts
|

Significantly different effects of tetrahydroberberrubine enantiomers on dopamine D1/D2 receptors revealed by experimental study and integrated in silico simulation

Abstract: Tetrahydroberberrubine (TU), an active tetrahydroprotoberberines (THPBs), is gaining increasing popularity as a potential candidate for treatment of anxiety and depression. One of its two enantiomers, l-TU, has been reported to be an antagonist of both D1 and D2 receptors, but the functional activity of the other enantiomer, d-TU, is still unknown. In this study, experiments were combined with in silico molecular simulations to (1) confirm and discover the functional activities of l-TU and d-TU, and (2) system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In our study, sufficient simulation time (200 ns) was applied to observe the protein conformational changes, which could also be used to investigate more complex transmembrane proteins. In particular, the same time-scale protocol was already implemented in various studies to analyse transmembrane dopamine D1/D2 receptors or some multidrug resistance proteins 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, sufficient simulation time (200 ns) was applied to observe the protein conformational changes, which could also be used to investigate more complex transmembrane proteins. In particular, the same time-scale protocol was already implemented in various studies to analyse transmembrane dopamine D1/D2 receptors or some multidrug resistance proteins 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The dopaminergic D1 receptor (PDB ID 7CKW), obtained from the PDB Data Bank, is crystallized with the catechol agonist fenoldopam. According to the literature, the active site of D1 receptor agonists and antagonists act on the same active site, and residues Asp103, Trp 321, Phe 289, Phe 288, Trp 285, Asn 292, and Ser 202 are considered the most influential for antagonist activity at the D1 receptor [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In AD, the effective ingredient of berberine hydrochloride berberine has been found to inhibit β / γ -secretion, increase α -secretion, and lessen A β levels in the hippocampus of AD mice, thereby improving cognitive impairment [ 6 ]. In patients with inflammatory bowel disease, berberine has been shown to stimulate dopamine α 2 and α 1 receptors [ 7 ]. The latest study [ 8 ] has confirmed that the striatal dopamine levels were elevated as measured by laser desorption mass spectrometry and berberine enhanced the imaging intensity of brain dopamine in mice receiving oral enterococci.…”
Section: Introductionmentioning
confidence: 99%